Populism and International Relations: (Un)predictability, personalisation, and the reinforcement of existing trends in world politics. Issue 5 (18th June 2019) - Destradi, Sandra; Plagemann, Johannes
Abstract: As populists have formed governments all over the world, it becomes imperative to study the consequences of the rise of populism for International Relations. Yet, systematic academic analyses of the international impact of populist government formation are still missing, and political commentators tend to draw conclusions from few cases of right-wing populism in the Global North. But populism – conceptualised as a 'thin' ideology based on anti-elitism and anti-pluralism – takes different shapes across world regions as populists combine it with different 'thick' ideologies. To reflect such diversity and gain more systematic insights into the global implications of populism, we focus on cases of populist government formation in the Global South. We find that populists in power are not, per se, more belligerent or less willing to engage globally than their non-populist predecessors. Factors like status seeking or a country's embeddedness in international institutions mitigate the impact of populism. Its most immediate effect concerns procedural aspects: foreign policymaking becomes more centralised and personalised – yet, not entirely unpredictable, given the importance of 'thick' ideologies espoused by populist parties and leaders. Rather than changing course entirely, populists in power reinforce existing trends, especially a tendency towards diversifying international partnerships.